"THE GENDER OF LAW: analysis of practices and institutions", organized by Camila Silva Nicácio and Júlia Silva Vidal - Perissinotto de Almeida, Gabriela (Universidade de Brasília, 2021)
Review of the book “The Gender of Law. Analysis of practices and institutions”, organized by Camila Silva Nicácio and Júlia Silva Vidal.